Hepatic encephalopathy for the hospitalist. Issue 8 (7th March 2016) - Sweigart, Joseph R.; Bradley, Bruce; Grigorian, Alla Y.
Abstract : The care of patients with advanced liver disease is often complicated by episodes of acute decline in alertness and cognition, termed hepatic encephalopathy (HE). Hospitalists must be familiar with HE, as it is a common reason for hospitalization in this population and is associated with significantly increased mortality. This narrative review addresses common issues related to diagnosis and classification, precipitants, inpatient management, and transitions of care for patients with HE. The initial presentation can be variable, and HE remains a clinical diagnosis. The spectrum of HE manifestations spans from mild, subclinical cognitive deficits to overt coma. The West Haven scoring system is the most widely used classification system for HE. Various metabolic insults may precipitate HE, and providers must specifically seek to rule out infection and bleeding in cirrhotic patients presenting with altered cognition. This is consistent with the 4‐pronged approach of the American Association for the Study of Liver Disease practice guidelines. Patients with HE are typically treated primarily with nonabsorbable disaccharide laxatives, often with adjunctive rifaximin. The evidence for these agents is discussed, and available support for other treatment options is presented. Management issues relevant to general hospitalists include those related to acute pain management, decisional capacity, and HE following transjugular intrahepatic portosystemic shunt placement. These issues are examined individually. Successfully transitioning patients recovering from HE to outpatient care requires open communication with multiple role players including patients, caregivers, and outpatient providers. Journal of Hospital Medicine 2016;11:591–594. © 2016 Society of Hospital Medicine